Estudio de la satisfacción de los clientes con el producto rompope en la microempresa Marialy de la ciudad de Calceta - Meza Zambrano, Erika Tatiana (2014)
This research was conducted in the Microenterprise Marialy located in the province of Manabí, Bolívar canton, city of Calceta, on August 10th street via Quiroga. The evaluation consisted in the improvement of customer satisfaction with the eggnog product, interview technique was used to the head of sales, which yielded favorable responses to the questions raised about the theme. Likewise; a survey was applied to people who consume eggnog, where more information about the failures was obtained. It was designed using the Delphi method based on the criteria of 10 experts who have knowledge of customer satisfaction, these surveys yielded three main problems with the product among the drawbacks around the changes in taste of the product, bad presentation, and price not subjected to quality. Different observations were made to the local store, where the product should have an attractive presentation, good hygiene, and good deal to the customer. Finally the owners proposal was provided to improve each of the problems presented by this study, so the quality of the product being offered to customers and thus get satisfied consumers.